Induced biochemical changes due to seed bacterization by Pseudomonas fluorescens in maize plants - R.C. SHARMA, G. SIVAKUMAR1* and (Indian Phytopathology, 2003)
Biochemical changes in banded leaf and sheath blight affected maize plants caused by Rhizoctonia solani f.sp. sasakii grown out of seeds treated with Pseudomonas fluorescens were studied. There was an increase in phenolic content in maize leaf sheaths inoculated with R.solani or in those of maize plants raised from P. fluorescens- treated seeds. Increase in phenolic content was also observed, in leaf sheaths of plants raised from P. fluorescens treated seeds when inoculated with R.solani. Peroxidase (PO), polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL) activities increased when leaf sheaths were inoculated with the pathogen and plants raised from P.fluorescens- treated seeds showed higher activity. However leaves from P. fluorescens treated seeds did not show any further increase in the PO and PPO activities after inoculation with R.solani. The bacterized seed with P.fluorescens lead to accumulation of higher phenolic compounds and higher activity of PO, PPO and PAL, that may playa role in defense mechanism in plants against pathogen.